A review of the impact of early tracheostomy among head injury patients - Mohamed Ludin, Salizar; Mahmud, Muhammad Farhan (Atlantis Press International B.V, 2021)
Individual who suffers from a head injury required a specific plan of treatment and nursing care to achieve the best outcome they could have. The initiation of tracheostomy is one of the interventions that may be executed on head injury patients especially for those with prolonged respiratory issues. Early tracheostomy (ET) is believed to offer a significant positive impact compared to late tracheostomy (LT). The objectives of this literature search are to determine past studies regarding the evaluation of the tracheostomy approach among head injury patients and identify the gaps of knowledge on the initiation of tracheostomy and head injury patients. The information and past research on the topic of tracheostomy and head injury were identified according to the systematic review PRISMA approach from multiple online databases which are PubMed, Science Direct, Springer Link, and ProQuest. Recent articles from the last decade of 2010-2020 had been identified to explore the practice and outcome of tracheostomy among head injury patients. There are 17 studies were included which discussed the impact of the tracheostomy approach and 15 of the studies in which a total of 6, 705 patients were really focused on the comparison between ET (n=3189) and LT (n=3516) among head injury patients. The definition of ET was varied between the studies, but it is within the range of fewer than 7 days for ET. ET had reported significant findings in reducing the duration of mechanical ventilation, reducing the duration of ICU stay, better functional outcome, and faster decannulation rate. On the other hand, most of the past studies had shown that ET was not significant in reducing the mortality rate of the patients. The initiation of ET does contribute a good outcome for the head injury patients in terms of the duration of mechanical ventilation and ICU stay. However, the association between ET with overall hospitalization duration, the incident of pneumonia, and the mortality rate are still inconclusive. The review also shows that ET contributes to a better functional outcome.